Dynamic activation of the anterior cingulate cortex during anticipatory anxiety - Straube, Thomas; Schmidt, Stephanie; Weiss, Thomas; Mentzel, Hans-Joachim; Miltner, Wolfgang H. R. (NeuroImage, 2009)
Based on theoretical models, we investigated the dynamics of brain activation during anticipatory anxiety using functional magnetic resonance imaging and a combined parametric/correlational design. Subjects (16 females) anticipated the application of electrical shocks of varying intensity resulting in four different threat levels. The parametric analysis revealed an inverted U-function of activation in the ventral anterior cingulate cortex (ACC) depending on the level of threat. Furthermore, the correlation analysis showed that the association between anxiety and brain activation in the pregenual ACC was, as a tendency, positive during moderate threat but clearly negative during strong threat. Moreover, during strong threat, a positive correlation between anxiety and activation was observed in the dorsal ACC, somatosensory cortex, motor cortex, and hippocampus. These findings suggest threat dependent dynamics of brain activation in the ACC; with increased attentional avoidance during moderate threat and a switch to hypervigilant action readiness in the most anxious subjects during strong threat. © 2008 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: ACC; Anticipation; Brain; Fear; Pain